Harrison's principles of internal medicine - Jamson, J. Larry; Fauci, Anthony S.; Kasper, Dennis L. (McGraw Hill, 2018)
This book, chapter 1 begins with an overview of "The Practice of Medicine". Part 2, "Cardinal Manifestations and Presentation of Diseases" is a signature feature of Harrison's.